Penilaian Tingkat Risiko Keselamatan Jalan Pada Jalur Pariwisata - Yogi Oktopianto; Rizky Dwi Anggara (Borneo Engineering : Jurnal Teknik Sipil, 2022)
Tourism is a journey made from one place to another with the intention of doing sightseeing and recreation. The tourism area has a very important role to improve the economy for the local community. Many tourism activities depend on transportation. To support smooth access to tourist attractions, good facilities and infrastructure are needed. Good infrastructure in this case is needed to facilitate accessibility, reduce accident rates and avoid the risk of fatal accident victims. The study was conducted to analyze the level of road risk categories in the Dieng tourism route. The method used in collecting data in this study was to conduct a survey using the Hawkeye 2000 series and the Hawkeye Data Processing Toolkit software was used to analyze the data. From the results of the analysis, it was found that the tourism route section contained an aspect of the road geometric with a moderately dangerous risk category (CB), namely Roughness/IRI and for the aspect of harmonization of road equipment there was a very dangerous category (SB), namely lane width, road shoulder width. , and street lighting which on this route has technical deviations and high accident probability and impact. The road safety risk on the Kajen–Dieng tourism route is Moderately Dangerous (CB) with a risk level of 127.